1995
DOI: 10.1073/pnas.92.4.978
|View full text |Cite
|
Sign up to set email alerts
|

Adherence of human immunodeficiency virus-infected lymphocytes to fetal placental cells: a model of maternal --> fetal transmission.

Abstract: The precise timing and mechanism of in utero human immunodeficiency virus (HIV) infection are unknown, but transplacental transmission is likely. Term placentas from HIV+ pregnancies contain only rare HIV-infected cells whose origins and phenotypes remain controversial, and no correlation has been found between the presence of HIV in term placentas and transmission to offspring. Reports of trophoblast infectibility have not been reproducible and do not address the question of infection in the placental stroma,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 33 publications
0
10
1
1
Order By: Relevance
“…The most topical of these pathogens are the human lentiviruses, which can be transmitted in utero [27,28]. It has been suggested that fetal trophoblast cells and placental macrophages may be important components promoting intrauterine infections [29][30][31]; however, our model would support direct infection of the fetus rather than infection of the placenta.…”
Section: Discussioncontrasting
confidence: 54%
“…The most topical of these pathogens are the human lentiviruses, which can be transmitted in utero [27,28]. It has been suggested that fetal trophoblast cells and placental macrophages may be important components promoting intrauterine infections [29][30][31]; however, our model would support direct infection of the fetus rather than infection of the placenta.…”
Section: Discussioncontrasting
confidence: 54%
“…The transmission of maternal cells could also be responsible for the vertical transfer of infectious agents, such as HIV-1 [23,24]. The transfer of a natural killer-cell lymphoma from mother to fetus has also been described [25].…”
Section: Introductionmentioning
confidence: 96%
“…It appears that the phe notype of the virus and the type of the cell involved in such assays may deviate from the expected outcome into the opposite direction as human antibodies which were effective in vitro were not capable of neutralizing the same virus in vivo [47], Despite the progress in anti-HIV vaccine development, very little is known about the pro tective effects of neutralizing Abs against the spread of HIV to the tissues outside of the blood compartment. Schwartz et al [48] suggested recently that polyclonal Abs and soluble CD4 can block cell-mediated HIV infection in chorionic villus cultures. However, these primary cul tures consisted of mesenchymal fibroblastoid cells located beneath the trophoblast layer, which constitutes the outer surface of the placenta.…”
Section: Failure Of Hiv Antibodies To Protect Placental Trophoblastsmentioning
confidence: 99%